THE USE OF BUGINESE ANCESTORS’ MESSAGES PEMAKAIAN SIMBOL-SIMBOL BUGIS DALAM PAPPASENG TO-RIOLO - Kamaluddin, Kamaluddin (Jurnal Noken: Ilmu-Ilmu Sosial, 2017)
This research study of symbolism in Buginesse ancestors message specially in Pappaseng tau Riolo. A packet of message of the old man testament in Buginisse Tribe. In getting the truly and accurate data, the writes used the library research which is to obtain more theoretical principles needed in the writing of this study. The writer reads some books and other materials which are closely related to the main problem of this writing. The writer discusses in the Semantic side. By analyzing the semantic, we will know the meaning those contents in the Pappaseng. And also we can know what is the main meaning and the aim of using that symbol.